Revisiting Myth in the Sphere of Gendered Objectification: An Analysis of the Poem “Helen of Troy does Countertop Dancing” by Margaret Atwood - A.N. Sreelakshmi; Susan Sanny (Comparative Literature: East & West, 2022)
ABSTRACTPoetry is a literary form where the poet expresses himself or herself through the representations they have carved. It defines a literary expression where the beliefs and perceptions get represented using mythical aspects to enhance cultural meanings. Margaret Atwood is well-known for using mythical female characters in her poems by placing them in the contemporary sphere. As Guerin once remarked, a tribe or a country might come together through mythology to engage in shared psychological and spiritual pursuits. The female characters which Atwood brings into her poems are metaphors representing the socio-political and cultural state of the modern era in which females are placed now in the present times. In her poem, “Helen of Troy Does Countertop Dancing,” Atwood brings in the historical figure of the famous Helen of Troy, who is well known in the literary domain for her beauty which formed the basis for the Trojan War. The paper argues how the aspect of revisiting myth in the poem trounces objectification by using the notion of female resistance.